CEST MRI detects antiretroviral drug toxicities in the developing mouse brain - Summerlin, Micah; Uberti, Mariano G.; Shinde, Dhananjay; Foster, Emma G.; Sillman, Brady; Kumar, Manjeet; Yao, Baojin; Peng, Dongming; Edagwa, Benson J.; Gendelman, Howard E.; Liu, Yutong; Bade, Aditya N. (Frontiers in Pharmacology, 2025)
Advances in antiretroviral drugs (ARVs) have achieved remarkable success in preventing gestational human immunodeficiency virus type 1 (HIV-1) transmission from mother to fetus. This is reflected in the rising numbers of HIV-1-exposed uninfected (HEU) children. Worldwide, the number of HEU children exceeds sixteen million, with more than one million children joining this group each year. Although HEU children remain uninfected, they are at an increased risk of neurodevelopmental deficits. Notably, in utero exposure to HIV-1 and ARVs is a causative factor. Both are linked to adverse neurodevelopment, warranting close clinical monitoring and therapeutic intervention. We now demonstrate that chemical exchange saturation transfer (CEST) MRI can be used to successfully monitor in utero ARV-exposure-associated embryo brain metabolomic and macromolecular dysregulations in a mouse model. CEST hyperintensities at −3.5 ppm (nuclear Overhauser effect) and 3.5 ppm (amide/amine protons) are measured in the brains of mouse embryos exposed to dolutegravir (DTG). These reflect DTG-induced alterations in cellular membrane lipids, mobile proteins or peptides, and glutamate levels. All demonstrate impaired neuronal development. Non-targeted metabolomics confirms the CEST results. These support the observations of DTG-induced differential expression of lipids and metabolites that reflect deficits in energy production, cell metabolism, post-translational protein modifications, and transport pathways. Furthermore, CEST MRI demonstrated the therapeutic benefits of long-acting nanoformulation delivery of DTG in mitigating neurodevelopmental impairments. These data, taken together, support the utility of CEST MRI as a non-invasive imaging biomarker for detecting neurodevelopmental deficits.